Associations between brominated flame retardants exposure and non-alcoholic fatty liver disease: Mediation analysis in the NHANES - Yulan Cheng; Jingyi Su; Xiangdong Wang; Ruiyao Huang; Zixuan Zhao; Kai Tian; Tianxiang Gu; Xiaoke Wang; Lin Chen; Xinyuan Zhao (Ecotoxicology and Environmental Safety, 2025)
Background: Exposure to brominated flame retardants (BFRs) may negatively impact human health. The association of BFRs with nonalcoholic fatty liver disease (NAFLD) in the general population is unclear. Meanwhile, limited studies have investigated the potential role of oxidative stress and inflammation in this link. Methods: We included 4110 adults from the 2009–2014 National Health and Nutrition Examination Survey (NHANES). NAFLD was diagnosed by serum alanine aminotransferase (ALT), hepatic steatosis index (HSI), and United States fatty liver index (USFLI). The link between a single BFR exposure and NAFLD was estimated using weighted logistic regression and restricted cubic splines (RCS). The quantile-based g-computation (QGC), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) were applied to evaluate the overall correlation of BFRs mixtures with NAFLD and identify significant compounds. Furthermore, we investigated the potential mediation function of oxidative stress and inflammation. Results: Our study demonstrated that specific concentrations of BFRs are related to an increased risk of NAFLD, both individually and when combined. PBB153, PBDE28, PBDE209, and PBDE153 exhibited the highest importance for NAFLD and were potential risk factors worthy of concern. Additionally, mediation analysis showed that absolute neutrophil cell count (ANC) and lymphocyte count (LC) (inflammation markers) have significantly mediated influences on the correlations of PBB153, PBDE85, and PBDE28 with N AFLD risk. Albumin (ALB) (oxidative stress marker) has notably mediated influences on the correlations of PBDE99, PBDE154, and PBDE85 with NAFLD risk. Men had higher serum BFRs concentrations than women, and the association between BFRs and NAFLD was also more prominent in men, which may be related to physiological differences between the sexes. Conclusions: Our findings offer evidence for single and mixed associations of BFRs and NAFLD in ordinary US adults. Furthermore, oxidative stress and chronic inflammation may mediate the effects of BFR exposure on NAFLD development.